Heartland Virus in Lone Star Ticks, Alabama, USA - Newman, Brent C.; Sutton, William B.; Moncayo, Abelardo C.; Hughes, Holly R.; Taheri, Ali; Moore, Thomas C.; Schweitzer, Callie J.; Wang, Yong (Emerging infectious diseases, 2020)
We detected Heartland virus (HRTV) in lone star nymphs collected in 2018 in northern Alabama, USA. Real-time reverse transcription PCR selective for the small segment of the HRTV genome and confirmatory sequencing of positive samples showed high identity with HRTV strains sequenced from Tennessee and Missouri.